Depression Is Associated With Constipation in Patients With Parkinson's Disease - Xiao-ling, Qin; Gang, Chen; Bo, Lu; Zai-li, Li; Xue-kui, Liu; Xue, Li; Ming-yu, Shi; Yin-zhen, Du; Xu, Chen; Dian-shuai, Gao (Frontiers in Neurology, 2020)
Objective: Constipation is one of the most frequent non-motor symptoms (NMS) in Parkinson’s disease (PD), causing great disturbance to patients. The present study investigated prevalence and clinical features of constipation in patients with PD, and explored the difference between prodromal and clinical constipation of PD. Methods: 186 patients with PD were recruited into this study. Subjective constipation was defined by ROME III criteria. Demographic and PD related clinical information of the participants was collected. PD patients were objectively assessed by a spectrum of rating scales of motor symptoms, non-motor symptoms, and quality of life. Results: Totally 51.61% (96/186) PD patients suffer from constipation. Compared with patients without constipation, patients with constipation were prone to have RLS, depression and anxiety, and have higher scores of NMSS. Among patients with constipation, 21.88% (21/96) patients had constipation in prodromal stage. Compared with patients with constipation in clinical stage, patients with prodromal constipation had lower age of constipation onset（56.48±9.63 and 65.26±8.42, χ2=4.091，P<0.001）, longer timespan from constipation onset to motor symptom onset (6.62±3.91 and 3.18±2.13, χ2=-3.877, P=0.001). Patients with prodromal constipation were predominantly tremor onset (χ2=4.405, P=0.044), and usually had better quality of life (28(14.50~37.5) and 40(25.0~55.0), χ2=2.011, P=0.046). Depression was the only risk factor of constipation in PD patients. BMI, depression, and anxiety were factors that affected the life quality in patients with constipation. Conclusions: Our results supported the high incidence of constipation in patients with PD, and that some constipation occurred before the onset of motor symptoms. Specific clinical characteristics of patients with constipation and with prodromal constipation help to make early diagnosis, to discover the relationship between constipation and PD, and to further explore the pathogenesis of this degenerative disease.